Transformasi Digital Adopsi Software As a Service Layanan Cloud Accounting oleh UMKM - Endar Pradesa; Tiara Syahrani; Ratih Eka Sakti (BUDGETING : Journal of Business, Management and Accounting, 2023)
The purpose of this study is to explore and explore the decision to adopt or not adopt Software as a Service by Micro, Small and Medium Enterprises in Lubuklinggau City. This research uses a qualitative approach with an exploratory research design. Researchers collected primary data using in-depth interview techniques with 12 informants from 6 MSE’S sectors that most dominate businesses in Lubuklinggau City. The results of the study show that the adoption of Software as a Service innovation in the form of cloud accounting services in Lubuklinggau City is still relatively low. Personally, MSE’S players are still at the awareness and interest stage. Meanwhile, as a business group, MSMEs in Lubuklinggau City are still at the level of the early majority to the late majority and can even reach the laggard. Factors that influence the adoption of cloud accounting service innovations for MSE’S in Lubuklinggau City, namely: 1) Supporting factors, namely the ease of accessing and inputting data and effectiveness in business operations. 2) The inhibiting factors are the weak ability to understand technology, lack of competent human resources, limited financial data, and weak business management. Weak ability to understand technology into performance expectancy, lack of competent resources, and financial data is still a little bit into facilitating conditions and weak business management into effort expectancy. Keywords : Adoption Innovation, Digital Transformation, Software as a Service.